Economic Insanity. (23rd June 2021) - Obeng‐Odoom, Franklin
Abstract: Richard Giles, a leading Australian Georgist political economist, suggests that criticisms of mainstream economics can be reduced to three: neglect of the Physiocrats, rejection of Georgist political economy, and the attempted revival of Georgist land economics with faulty variants of those principles. Yet, in defending Georgism, Giles fails to show it can resolve the legacies of chattel slavery, colonialism, and neocolonialism. Despite that limitation, Giles shows that the renewal of land economics is essential to achieving economic justice. Along the way, Giles provides original insights about the limitations of modern monetary theory, the Malthusian economics of global migration, and the rise of global nationalism.